Graphene-coated nanoporous nickel towards a metal-catalyzed oxygen evolution reaction. Issue 24 (15th June 2021) - Qiu, Hua-Jun; Johnson, Isaac; Chen, Luyang; Cong, Weitao; Ito, Yoshikazu; Liu, Pan; Han, Jiuhui; Fujita, Takeshi; Hirata, Akihiko; Chen, Mingwei
Abstract : We report that high OER activity can be achieved from the metallic state of Ni which is passivated by atomically thick graphene in a three-dimensional nanoporous architecture. Abstract : Developing highly active electrocatalysts with low costs and long durability for oxygen evolution reactions (OERs) is crucial towards the practical implementations of electrocatalytic water-splitting and rechargeable metal–air batteries. Anodized nanostructured 3d transition metals and alloys with the formation of OER-active oxides/hydroxides are known to have high catalytic activity towards OERs but suffer from poor electrical conductivity and electrochemical stability in harsh oxidation environments. Here we report that high OER activity can be achieved from the metallic state of Ni which is passivated by atomically thick graphene in a three-dimensional nanoporous architecture. As a free-standing catalytic anode, the non-oxide transition metal catalyst shows a low OER overpotential, high OER current density and long cycling lifetime in alkaline solutions, benefiting from the high electrical conductivity and low impedance resistance for charge transfer and transport. This study may pave a new way to develop high efficiency transition metal OER catalysts for a wide range of applications in renewable energy.